2010
DOI: 10.1094/phyto-100-5-0474
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the Mating Type and Toxin Production Genes in Pyrenophora tritici-repentis

Abstract: Pyrenophora tritici-repentis, the causal agent of tan spot on wheat, is a homothallic loculoascomycete with a complex race structure. The objectives of this study were to confirm the homothallic nature of the pathogen, characterize mating type diversity and toxin production genes in a global collection of strains, and analyze how these traits are associated between each other and with existing races. The pseudothecia production capacity, race identification, mating type locus (MAT), internal transcribed spacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 49 publications
1
44
0
3
Order By: Relevance
“…This ongoing study of virulence of P. tritici-repentis isolates in Mexico indicates race 1 is the most predominant race of the tan spot fungus. Race 2 isolates not yet observed in our study have been previously observed in Mexico (Lepoint et al 2010). The findings of this study confirm to previous race analysis studies (Lamari & Bernier 1989c) which observed race 1 isolates to be the most predominant race.…”
Section: Resultssupporting
confidence: 92%
“…This ongoing study of virulence of P. tritici-repentis isolates in Mexico indicates race 1 is the most predominant race of the tan spot fungus. Race 2 isolates not yet observed in our study have been previously observed in Mexico (Lepoint et al 2010). The findings of this study confirm to previous race analysis studies (Lamari & Bernier 1989c) which observed race 1 isolates to be the most predominant race.…”
Section: Resultssupporting
confidence: 92%
“…Several studies included tools for detection variability www.intechopen.com using of morphocultural, pathogenic, bioquemical and molecular variability. Several studies to detect variability include different tools, the most of them used pathogenic and genetic characterization (PCR techniques) (Ali et al, 2010;Andrie et al, 2007;Friesen et al, 2005;Leisová et al, 2008;Lepoint et al, 2010;Litcher et al, 2002;Mehta et al, 2004;Moreno et al, 2009;Pujol Vieira dos Santos et al 2002;Singh & Hughes 2006). A lesser extent of research focuses on characterization based on morphological and biochemical aspects (Diaz de Ackermann 1987; Gilchrist et al, 1984;Hosford, 1971;Hunger & Brown 1987, Moreno et al, 2008aPujol Vieira dos Santos et al, 2002).…”
Section: Current Status Of Pyrenophora Tritici-repentismentioning
confidence: 99%
“…There are numerous works that refer to the population structure of P. tritici-repentis in races Andrie et al, 2007;Lepoint et al, 2010;Manning et al, 2002;Strelkov et al, 2002;Lamari et al, 2003;2005 ). Some of these papers involve aspects as morpholocultural and virulence variability (Ali et al, 2010).…”
Section: Current Status Of Pyrenophora Tritici-repentismentioning
confidence: 99%
See 2 more Smart Citations